Kant’s Justification of Welfare (Diametros, 2014)
For several decades, theorists interested in Kant’s discussion of welfare have puzzled over Kant’s position on the issue of the redistribution of goods in society. They have done this both in order to clarify his position and as a source of inspiration for current conceptual problems faced by contemporary political philosophers who attempt to reconcile the ideal of equal freedom with the asymmetric interference necessary for redistribution and social provision.In this paper, I start with Kant’s brief discussion of welfare in Rechtslehre and I identify four claims that Kant clearly asserts as characteristic for his view. I then outline five main interpretative directions in the literature, I evaluate and rank them. The most accurate view of Kant’s justification of welfare, which I call the “genuinely Kantian” position is, however, unable to explain the nature of the duty of welfare that it asserts. By going back to Kant’s text, I suggest one solution. This solution, together with some further questions, can be seen as initiating a new interpretative direction in the literature.